Interleukin-2 gene promoter polymorphism (T330G) and lymphocyte platelet adhesion in influenza A (H3N2) - G. A. Chuprova; A. N. Emel’yanova; A. S. Emel’yanov; Yu. A. Vitkovskii (Журнал инфектологии, 2022)
Introduction. Polymorphism of cytokine genes is a factor of susceptibility or resistance to infection, the development of the disease and a long, complicated course of influenza.Objectives. Study of the lymphocyte-platelet adhesion function in patients with influenza A (H3N2) depending on polymorphic variants of the IL-2 gene promoter (T330G).Materials and methods. The study included patients with influenza. Determination of SNP genes was carried out by PCR using standard kits of the Scientific and Production Company “Litekh” (Moscow). The examine of LPA was carried out by the method of Yuri Vitkovsky et al. (1999).Results. During the immunogenetic study the effect of the polymorphism of the IL-2 gene promoter (T330G) on the function of lymphocyte-platelet adhesion in patients with influenza A(H3N2) was studied. It was found that in the group of patients with influenza the occurrence of polymorphic variants of IL-2 (T330G) significantly differed from the control group.The major T allele significantly prevailed in patients compared with the group of healthy individuals with the predominance of the homozygous T/T genotype of the IL-2 gene promoter (T330G) (2.2 times) compared with the control group.Conclusions. Indicators of the function of lymphocyteplatelet adhesion in influenza A(H3N2) depend on the carriage of genotypes of the IL-2 gene promoter polymorphism (T330G).